Controlled Gene Gun Delivery and Expression of DNA Within the Cornea. (September 1997) - Tanelian, D.L.; Barry, M.A.; Johnston, S.A.; Le, T.; Smith, G.
Selective delivery of genes to ocular tissues in vivo has been a long sought after goal for potential gene therapy of ocular disease. The gene gun was considered for this purpose because of its ability to focally transfer DNA to cells through gold microparticles coated with DNA. Through experimentation, we optimized a technique that allows focal delivery and expression of a plasmid encoding green fluorescent protein in the corneal epithelium 100% of the time. Though the corneal epithelium has a delicate structure, this introduction was not associated with any corneal or ocular damage and did not produce any apparent ocular irritation. These findings demonstrate the utility of gene gun delivery of DNA to selected ocular tissues for potential experimental and therapeutic purposes.